2015
DOI: 10.1186/s41016-015-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of middle cerebral artery (MCA) aneurysms: a review of the literature

Abstract: Microsurgical treatment is well established as the preferred strategy for definitive obliteration of middle cerebral artery (MCA) aneurysms. However, increasing reports on the feasibility and efficacy of endovascular treatment of MCA aneurysms in large case series suggest coiling as a viable alternative to microsurgery. This review provides a critical overview of the current literature regarding MCA aneurysm treatment, with the objective to clarify the available evidence of efficacy with microsurgical compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…The reviewed surgical series reported occlusion rates between 90 and 89.3% with good clinical outcomes in 92–100% of unruptured and 70–80% of ruptured MCA aneurysms treated with clipping. The authors also suggested that the significantly higher retreatment rated and lower occlusion rates of the endovascular approach would offset the favorable clinical outcome in the short term of the less invasive approach ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed surgical series reported occlusion rates between 90 and 89.3% with good clinical outcomes in 92–100% of unruptured and 70–80% of ruptured MCA aneurysms treated with clipping. The authors also suggested that the significantly higher retreatment rated and lower occlusion rates of the endovascular approach would offset the favorable clinical outcome in the short term of the less invasive approach ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The middle cerebral artery was chosen for this project because approximately 14.0%–43.0% of all cerebral aneurysms in humans occur at sites associated with this artery . The concentration of vasopressin used in our experiments (1.4 × 10 −11 mol/L) is comparable to that observed in plasma and cerebrospinal fluid of the patients with SAH and is below the threshold for vasoconstriction of cerebral blood vessels in physiological conditions.…”
Section: Discussionmentioning
confidence: 93%
“…This rate is lower than the occlusion rates reported with clipping (> 90%) in most studies. 26 Clinical data should demonstrate better or similar results than clipping to challenge surgical management.…”
Section: Discussionmentioning
confidence: 99%